Polar Bears and Seals in the Eastern Beaufort Sea and Amundsen Gulf: A Synthesis of Population Trends and Ecological Relationships over Three Decades - Stirling, Ian (ARCTIC, 2002)
In the eastern Beaufort Sea and Amundsen Gulf, research on polar bear populations and their ecological interrelationships with seals and sea ice conditions began in the fall of 1970. Analysis of movement data from mark-recapture studies and tracking of adult female bears with satellite radio collars indicated that there are two populations of polar bears in the area, one that inhabits the west coast of Banks Island and Amundsen Gulf and a second that is resident along the mainland coast from about Baillie Islands in Canada to approximately Icy Cape in Alaska. Polar bears throughout the Beaufort Sea and Amundsen Gulf were severely overharvested before the establishment of quotas in Canada in 1968 and the cessation of all but subsistence polar bear hunting in Alaska in 1972. Since then, both populations have recovered, and the population estimates currently used for management purposes are 1200 and 1800 for the Northern and Southern Beaufort populations, respectively. However, these population estimates are now dated and should be redone. Most female polar bears in the Beaufort Sea breed for the first time at 5 years of age, compared to 4 years of age in most other populations, and cubs normally remain with their mothers for 2.5 years prior to weaning. Heavy ice conditions in the mid-1970s and mid-1980s caused significant declines in productivity of ringed seals, each of which lasted about 3 years and caused similar declines in the natality of polar bears and survival of subadults, after which reproductive success and survival of both species increased again. The changes in the sea ice environment, and their consequent effects on polar bears, are demonstrable in parallel fluctuations in the mean ages of polar bears killed each year by Inuit hunters. In 1989, the decadal-scale pattern in fluctuations of ice conditions in the eastern Beaufort Sea changed in response to oceanographic and climatic factors, and this change has resulted in greater amounts of open water in recent years. In addition, climatic warming will ...